Internalisasi Nilai Kewarganegaraan Berbasis Religiusitas melalui Kepemimpinan Visioner Kepala Sekolah di MI PAS Baitul Qur'an Indonesia - Zuhri, Saifudin; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to examine the strategic role of visionary leadership by the school principal in internalizing civic values integrated with Islamic religiosity at MI PAS Baitul Qur’an Indonesia. The research is motivated by the challenges faced by Islamic primary education in balancing the strengthening of religious identity with the formation of civic character aligned with Pancasila values. This research employed a qualitative approach with a case study design, utilizing participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted thematically through data reduction, data display, and conclusion drawing. The results indicate that the principal's visionary leadership is manifested through the formulation of the vision